PENINGKATAN MUTU PENDIDIKAN MADRASAH BERBASIS CUSTOMER DAN MODEL SIKAP FISHBEIN - M Mundir (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2016)
Research in the form of survey is aimed at making comparisons between the internal aspects of belief on the condition of Government Elementary School Nurul Athhar Kebonsari Benculuk Cluring Banyuwangi in East Java with aspects of internal evaluation, external aspect of belief with external aspects evaluation, internal aspect of belief with the external aspects of belief, the internal aspects of evaluation with external aspects of evaluation, and to know the different aspects of belief and evaluation aspects of internal customers and external customers. The survey was conducted using analytical models Fishbein. A survey of 30 customers showed different aspects of belief and evaluation aspects of internal customers and external customers. The survey results have implications for the necessity of minimizing the differences for the sake of fulfilling the expectations of internal and external customers to an educational institution, in order to realize improved service quality madrasah.Kata Kunci: Kepercayaan internal dan Eksternal, Evaluasi, Pelanggan